2017
DOI: 10.1021/acs.jpca.7b03907
|View full text |Cite
|
Sign up to set email alerts
|

Improved pKa Prediction of Substituted Alcohols, Phenols, and Hydroperoxides in Aqueous Medium Using Density Functional Theory and a Cluster-Continuum Solvation Model

Abstract: Acid dissociation constants (pK's) are key physicochemical properties that are needed to understand the structure and reactivity of molecules in solution. Theoretical pK's have been calculated for a set of 72 organic compounds with -OH and -OOH groups (48 with known experimental pK's). This test set includes 17 aliphatic alcohols, 25 substituted phenols, and 30 hydroperoxides. Calculations in aqueous medium have been carried out with SMD implicit solvation and three hybrid DFT functionals (B3LYP, ωB97XD, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
120
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 59 publications
2
120
1
Order By: Relevance
“…The p K a could be accurately determined by first-principles QM calculations employing the continuum/cluster model. For example, it was found that the SMD solvation method incorporating three explicit water molecules in the first solvation shell produced accurate p K a for molecules with hydroxyl and hydroperoxyl functional groups [ 27 ]. In the present study, the oxygen of the bridging ligand binds with the two copper ions, leaving the hydrogens of the bridging ligand pointing towards the outside of the active site.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The p K a could be accurately determined by first-principles QM calculations employing the continuum/cluster model. For example, it was found that the SMD solvation method incorporating three explicit water molecules in the first solvation shell produced accurate p K a for molecules with hydroxyl and hydroperoxyl functional groups [ 27 ]. In the present study, the oxygen of the bridging ligand binds with the two copper ions, leaving the hydrogens of the bridging ligand pointing towards the outside of the active site.…”
Section: Methodsmentioning
confidence: 99%
“…1 M and 1atm refer to the standard states for the aqueous solution and gas phase, respectively. G gas,H + is the gas-phase free energy of the proton with the value of −6.28 kcal/mol at the 1 atm standard state and 298.15 K [ 27 ]. ΔG 1atm→1 M is the free energy change from the standard state of 1 atm to 1 M, of which the value is 1.89 kcal/mol [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent examples of the merits of a hybrid type of approach can be illustrated by a series papers by Thapa and Schlegel . For a series of alcohols, phenols, hydroperoxides, thiols, and selenols, p K a calculations were carried out with different functionals and the SMD solvation model.…”
Section: Applicationsmentioning
confidence: 99%
“…Along this line, several works have been performed on proton‐transfer reactions in the gas phase as well as aqueous and non‐aqueous solution. For instance, Poliak applied the B3LYP/6–311++G(d,p) level of theory and IEF‐PCM/UFF solvation model to calculate the p K a values of the cationic acid aniline and pyridine derivatives in common solvents with the root‐mean‐squared (RMS) error of less than 2.0 p K a units .…”
Section: Introductionmentioning
confidence: 99%